Fuzzy Logic in Decision Support Systems Using Linear Equations in Construct 3 Game Engine - Sanriomi Sintaro (PT. Tech Cart Press, 2023)
The current use of Construct 3 is not only used as a tool for developing games but can also be developed to create applications that can run on platforms that support HTML5. However, the superiority of construct 3, which only requires logic without using program code, sometimes its rather difficult to develop when we need construct 3 to calculate mathematical algorithms such as Dijkstra or fuzzy. The problem that I found in this study is how to make Construct 3 can do some calculations using logic without program code to produce the required mathematical algorithm. The main purpose of this research is to find out the best way to be able to run Non-Linear equations into game engine Construct 3. The conclusion in this study is by using linear equations we can calculate the formula into the logic board in Construct 3, so the development of applications that require algorithms can be done in construct 3 without using programming code. Another conclusion is, the application development time is getting faster and more effective. This is proven by the fact that there is no need for program codes which are usually long and have different forms from the formulas that have been prepared.